ANALISIS PENERAPAN GOOD CORPORATE GOVERNANCE DALAM MENINGKATKAN KINERJA KEUANGAN PERUSAHAAN - Budi gautama Siregar (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2021)
The implementation of GCG is a concept that regulates the behavior of bank actors, namely company owners, management in carrying out their respective duties and responsibilities to minimize agency problems which in turn can improve the company's financial performance. This study aims to analyze the implementation of good corporate governance in improving financial performance at Islamic Commercial Banks for the 2012-2018 period. The study uses secondary data, namely the financial statements of Islamic Commercial Banks consistently published in the research period, namely 8 Islamic Commercial Banks. Based on the results of data analysis with the help of the eviews application, the results show that the implementation of good corporate governance has no effect on financial performance at Islamic Commercial Banks for the 2012-2018 period. Keywords: GCG, Financial Performance, BUS